Exploring the Sodicity Reclamation Efficiency of Coalchar: Exploring the sodicity reclamation efficiency of Coalchar - Kanagavalli, A; Sherene Jenita Rajammal, T; Baskar, M; Vanniarajan, C; Parthasarathi, R; Selvamurugan, M (Journal of Soil Salinity and Water Quality, 2025)
This study aimed to assess the impact of Coalchar application alone and in combination with gypsum, organic amendments like vermicompost (VC) and pressmud compost (PMC) on soil chemical properties, particularly pH, electrical conductivity (EC) and exchangeable sodium percentage (ESP) reduction in sodic soil. Here various treatments including: T1- absolute control (no amendment), T2-VC alone @ 2t ha-1, T3- PMC alone @ 3t ha-1, T4-gypsum alone @ 50% gypsum requirement (GR), T5- Coalchar alone @ 3t ha-1, T6- Coalchar +VC (1:1) @ 3t ha-1, T7- Coalchar + PMC (1:1 mixture) @ 3t ha-1, T8- Coalchar + gypsum (1:1mixture) @ 3 t ha-1 amendments were experimented in incubation study. Reclamation efficiency was evaluated based on the reduction in soil exchangeable sodium percent (ESP). Among the different treatments, the Coalchar + Gypsum (1:1) (based on Ca equivalence) combination showed the most significant reduction in ESP from 31.8 to 16.5% and soil pH from 8.92 to 7.92 over 30 days of incubation, and it was on par with the application of coalchar alone @ 3 t ha-1. Coalchar + Gypsum (1:1) treatment differed significantly from other treatments in reclamation parameters, with a reclamation efficiency of 50% ESP reduction over the absolute control (p< 0.05). The results demonstrate that coalchar alone or in combination with gypsum (1:1), can effectively reclaim sodic soils. These results provide that the field scale study be initiative for sodicity reclamation and in the legitimacy to the use of coalchar in sodic soil management as a partially viable and sustainable alternative to gypsum.